Fisetin Regulates Gut Microbiota and Exerts Neuroprotective Effect on Mouse Model of Parkinson’s Disease - Chen, Tian-Jiao; Feng, Ya; Liu, Te; Wu, Ting-Ting; Chen, Ya-Jing; Li, Xuan; Li, Qing; Wu, Yun-Cheng (Frontiers in Neuroscience, 2020)
Previous studies have reported the anti-oxidant, anti-inflammatory, and anti-cancer effects of fisetin. However, the therapeutic efficacy of fisetin in Parkinson’s disease (PD) is unclear. In this study, we demonstrated that fisetin could markedly alleviate 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced dopaminergic neurodegeneration in mice. To confirm the reported correlation between gut microbiota and PD, the bacterial DNA in the fresh feces of mice from each group was subjected to 16S rRNA (V3 and V4 regions) sequencing. The results revealed that fisetin changed the number, diversity, and distribution of gut microbiota in MPTP-induced mice model of PD. The alpha and beta diversity analyses showed that the fisetin intervented MPTP group gut microbiota exhibited a significantly higher abundance of Lachnospiraceae and a significantly lower abundance of uncultured_bacterium_g_Escherichia-Shigella and uncultured_bacterium_g_Bacillus than the MPTP group gut microbiota. These findings indicated that fisetin exerts a neuroprotective effect on neurodegeneration by altering the composition and diversity of gut microbiota. Thus, fisetin could be a potential novel therapeutic for PD.